2013
DOI: 10.1111/camh.12026
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and functional somatic symptoms: structural equations of a conceptual model

Abstract: Aims: To examine the effect of anxiety and parental overprotection on functional somatic symptoms (FSS) in children with attention deficit hyperactivity disorder (ADHD). Method: Seventy-six children and adolescents (aged 6-17) with ADHD and their parents completed a clinical interview about psychiatric and somatic symptoms. Parents also reported about parenting styles. Structural equation modeling (SEM) was used. Results: The generalized anxiety, overprotection, and specific phobia variables each had a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There is no significant difference between girls and boys in terms of somatic symptoms in this study. In a study, it was reported that generalized anxiety, phobia, and being a girl were risk factors for somatic symptoms in children with ADHD, and children with ADHD and somatic symptoms had more anxiety symptoms [ 19 ]. Also, children with ADHD and anxiety disorder had more physical symptoms than children with only ADHD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no significant difference between girls and boys in terms of somatic symptoms in this study. In a study, it was reported that generalized anxiety, phobia, and being a girl were risk factors for somatic symptoms in children with ADHD, and children with ADHD and somatic symptoms had more anxiety symptoms [ 19 ]. Also, children with ADHD and anxiety disorder had more physical symptoms than children with only ADHD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that 20% and 30% of adolescent girls had morning fatigue, stomachache, headache, and backache more than once a week [ 18 ]. Children and adolescents with ADHD diagnosis have somatic complaints; nevertheless, somatic complaints can be ignored by the clinicians [ 19 , 20 ]. In a study conducted with male adolescents aged 12-16 years, it was reported that adolescents with hyperactivity symptoms had more somatic complaints [ 20 ].…”
Section: Introductionmentioning
confidence: 99%